3D characterization of magnetic phases through neutron polarization contrast tomography - Busi, Matteo (2023)
The advancement of laser-based metal additive manufacturing has enabled the production of near net shape complex geometries. Understanding the microstructural features of materials is crucial for accurate modeling of their mechanical behavior, particularly with regard to strain- or thermal-induced martensitic phase transformations in ferrous alloys and steels. For example, the formation of BCC α′-martensite can strengthen materials while preserving ductility of the dominating austenitic phase. However, in components where the shape memory effect is attributed to the reversible formation of ε-martensite, the accumulation of deformation-induced α′-martensite is an undesired, irreversible degradation mechanism. This study presents a novel tomographic approach utilizing polarization contrast neutron imaging for the 3D volumetric characterization of magnetic crystallographic phases, especially those present in low phase fractions that are typically undetectable with traditional techniques. The technique is applied to the study of strain-induced martensitic phase transformations in additively manufactured lattice structures made of high-Mn steels, which form small fractions of α′-martensite upon deformation. The results demonstrate the value of this technique for characterizing entire components and complex geometries found in numerous technological applications.